Molecular Analyses of Aspirated Cystic Fluid for the Differential Diagnosis of Cystic Lesions of the Pancreas: A Systematic Review and Meta-Analysis - Xiaorong Guo; Xianbao Zhan; Zhaoshen Li (Gastroenterology Research and Practice)
Background. Researchers have evaluated various molecular tests for improving the differential diagnosis of cystic lesions of the pancreas. Methods. Six electronic databases were searched for articles on molecular tests for the diagnosis of pancreatic cysts. Measures of accuracy were extracted from selected articles and pooled by the random-effects model. Summary receiver operating characteristic curves were used to analyze the overall accuracy of the molecular tests. Pooled sensitivity and specificity values [95% confidence intervals] are reported. Results. The systematic review included eight studies of 428 patients in total. We determined the sensitivities and specificities of tests for KRAS mutations (0.47 [0.39–0.54], 0.98 [0.93–0.99]) and loss of heterozygosity (0.63 [0.54–0.71], 0.76 [0.63–0.87]) for distinguishing mucinous from nonmucinous cysts, as well as the sensitivities and specificities of tests for KRAS mutations (0.59 [0.46–0.71], 0.78 [0.71–0.85]) and loss of heterozygosity (0.89 [0.78–0.96], 0.69 [0.60–0.76]) for differentiating malignant from benign cysts. Conclusion. Tests of KRAS mutations could confirm but not exclude a diagnosis of a mucinous or malignant pancreatic cyst.